2015
DOI: 10.1038/nature15525
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the RNA-dependent RNA polymerase from influenza C virus

Abstract: Negative-sense RNA viruses, such as influenza, encode large, multidomain RNA-dependent RNA polymerases that can both transcribe and replicate the viral RNA genome. In influenza virus, the polymerase (FluPol) is composed of three polypeptides: PB1, PB2 and PA/P3. PB1 houses the polymerase active site, whereas PB2 and PA/P3 contain, respectively, cap-binding and endonuclease domains required for transcription initiation by cap-snatching. Replication occurs through de novo initiation and involves a complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
177
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 44 publications
14
177
0
Order By: Relevance
“…This is consistent with the location of the 627 domain on the outside of the polymerase core, which is made up of PB1, the C-terminal domain of PA, and an N-terminal third of PB2 (1113). The 627 domain is also not required for RNA template binding, as the RNA-binding functions reside in the polymerase core (12, 13).…”
Section: Discussionsupporting
confidence: 84%
“…This is consistent with the location of the 627 domain on the outside of the polymerase core, which is made up of PB1, the C-terminal domain of PA, and an N-terminal third of PB2 (1113). The 627 domain is also not required for RNA template binding, as the RNA-binding functions reside in the polymerase core (12, 13).…”
Section: Discussionsupporting
confidence: 84%
“…Nonetheless, the function of this loop region is not completely clear. It is suspected to interact with the viral genome in the resolved influenza B and C virus structures (46, 47, 84), and K198 of influenza A virus was suggested to be related to host adaptation (85). As the density of the loop region (residues 195 to 198) is missing from the influenza A virus polymerase crystal structure, we used kinematic loop modeling in the Rosetta software to computationally reconstruct the loop region (86).…”
Section: Resultsmentioning
confidence: 99%
“…The PB2 structure is shaded in green, and the possible interacting residues of PB1 are blue. The interface residues were predicted by the SASA changing upon complex formation with Sppider (84). Download …”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Adaptive mutations increase replication, pathogenicity, and transmission of avian-origin viruses in mammalian hosts. Structural analyses have revealed that portions of PB2, including the 627 domain, remain solvent exposed in the holoenzyme and undergo large-scale conformational reorganization depending on whether the polymerase is replicating or transcribing (Hengrung et al, 2015; Pflug et al, 2014; Reich et al, 2014; Thierry et al, 2016). These data raise the possibility that adaptive mutations in PB2 may be important for intra- or inter-molecular protein:protein interactions and conformational rearrangements.…”
Section: Introductionmentioning
confidence: 99%